Pengaruh Pengetahuan Nasabah , Reliogiousity Dan Lingkungan Sosial Terhadap Minat Menabung Menggunakan Bank Syariah (Studi Kasus Mahasiswa Universitas Islam Malang) - Dinda Dewi Anggraeni; Nur Diana; Harun Alrasyid (Universitas Islam Malang, 2022)
This study aims to determine and analyze the effect of customer knowledge, religiosity, and social environment oninterest in saving in Islamic banks among students of the Islamic University of Malang. The type of research used iscorrelational research. The sample in this study was 99 students of the Islamic University of Malang. Data wascollected by distributing questionnaires. Analysis of the data used in this study using validity test, reliability test,normality test, multicollinearity, heteroscedasticity, simultaneous F test, coefficient of determination, and t-testresults. The results of this study simultaneously the variables of customer knowledge, religiosity, and socialenvironment have a significant effect on interest in saving in Islamic banks. While partially 1) the variable ofcustomer knowledge partially has a significant positive effect on interest in saving, 2) religiosity partially has asignificant and positive effect on interest in saving, and the social environment partially has a significant andnegative effect on interest in saving.